Soil and water conservation on Central American hillsides: if more technologies is the answer, what is the question? - Hellin, Jonathan; López Ridaura, Santiago (American Institute of Mathematical Sciences, 2016)
Climate change is likely to lead to increased water scarcity in the coming decades and to changes in patterns of precipitation. The result will be more short-term crop failures and long-term production declines. Improved soil management is key to climate change adaptation and mitigation efforts. There is growing interest in the promotion of climate smart agricultural practices. Many of these are the same practices that were promoted in the 1980s and 1990s under the guise of soil and water conservation. Farmer non-adoption of soil conservation technologies was rife and suggests that different approaches are needed today. Much can be learnt from these past endeavors to ensure that current efforts are better designed and implemented. We use the example of Central America to highlight some of these lessons and suggest alternative ways forward. Technology per se is not the limiting factor; many suitable technologies and practices are extant. What is required is a more nuanced approach to soil conservation efforts. There is a need to focus less on capturing soil once it has been eroded, via the use of cross-slope soil conservation practices, and more on improving soil quality of the soil that remains through improved soil cover. It is also critical to understand farming systems as a whole i.e. the full range of interlinked activities and the multiplicity of goals that farm households pursue. Furthermore, it is important to engage farmers as active players in conservation efforts rather than passive adopters of technologies, and to adopt a board value chain approach and engage a plethora of value chain actors (researchers, extension agents, equipment manufacturers, input suppliers, farmers, traders, and processors) in an agricultural innovation system.